Change strategy in Spain: Ciudadanos vs Podemos - E. Kryukova; Yu. Slivchikova (Ибероамериканские тетради)
The article sets out to analyze the changing political reality in Spain perturbed by such emerged parties as Podemos and Ciudadanos. While the first one appeared riding on the wave of the massive protests of the «indignant» caused by consequences of the economic crisis and was organized around the populist strategy, the second one was created initially to defend the rights of the Spanish people in Cataluña and gaining popularity grew from the regional party into the national one. The fact that these two young parties could win so fast the credibility of the citizens shows the weakness of the existing Spanish bipolar political system. The authors pretend to compare the programs of both parties and try to predict their possible influence on the political, social and economic situation in Spain.